Auditoria electro-energética a la planta procesadora de cárnicos y embutidos "INAPESA" de la Ciudad de Loja. - Alarcón Padilla, Lorena Paulina (2005)
The Globalization in which we live and forces us to obtain maximum efficiency of electric power, conducting an audit Electro-Energy is of paramount importance, as it gives solutions to the problems of modern institutions and companies in managing effective prevention policies electrical difficulties are reflected in considerable economic losses and damage to the rest of the technological equipment. Besides that it opens our eyes to see economic potential such as energy saving. This research first established a methodology required to perform audits in electrical systems, this will constitute a series of concepts, theoretical foundations, standards and safety rules and calculation methods needed in the audit. This methodology is then applied to the industrial field, specifically the Processing Plant Sausages and Meat "INAPESA" where visual inspections, measurements and calculations of the main variables and parameters of the electrical distribution system of the company were made. a thorough analysis of historical energy consumption and costs that the entity had as payments for electricity consumption was made. the main circuits are studied and areas of higher consumption by areas are analyzed and an action plan for reducing this consumption is recommended. At work special attention is also paid to cold rooms and light levels in different areas of the plant. With this research will save 20% of the total fee payments under FP installing clearing banks calculated.